Effection gender on access contraception eligible women in region coastal Muslim Medan Area - Nanda, Meutia; Damanik, Nurliana; Nissa, Nur Ifani Chairun (BKM Public Health and Community Medicine, 2021)
Objective: This study aims to determine the influence of gender on access to contraception among women of childbearing age in the coastal slums of Medan City using multilevel spatial analysis. Methods: The study utilized a modified version of the 2017 Indonesian Demographic and Health Survey questionnaire, incorporating variables related to paternalistic gender influence. 600 respondents were involved, including 255 married men, 255 women, and 90 ward heads. Spatial analysis was conducted on the respondents' locations within the slums of Medan City. Data from the questionnaires were analyzed using the Chi-square test and multilevel linear regression, with a significance level of 0.000 < 0.005. Results: The findings indicate that gender significantly influences access to contraception among women of childbearing age in the coastal slums of Medan City. The analysis revealed that paternalistic gender norms and practices hinder women's access to family planning services. The difficult access to health service facilities and high transportation costs exacerbate this issue, leading to low community participation in family planning programs. Conclusion: Gender plays a crucial role in access to contraception in the coastal slums of Medan City. Efforts to improve family planning participation must address gender norms and provide more accessible and affordable contraceptive services.